Mediastinal hemangioma mimicking an invasive tumor growth: A case report. (March 2021) - Yobita, Shogo; Iizuka, Shuhei; Otsuki, Yoshiro; Nakamura, Toru
Highlights: Mediastinal hemangiomas may exhibit an infiltrating appearance. Extensive surgery is often required due to an inaccurate preoperative diagnosis. A hemangioma should be raised as a differential diagnosis to avoid extensive surgery. Abstract: Introduction and importance: Mediastinal hemangiomas are a rare entity frequently developing in the anterior mediastinum. They may exhibit an infiltrating appearance into the surrounding tissue, and extensive surgery is often required despite its benign nature. We report a case of a mediastinal hemangioma mimicking an invasive tumor growth requiring a combined resection of the lung and diaphragm. Case presentation: An asymptomatic 73 year-old-man presented with a 50 mm-sized mass on his chest radiography. A combined resection of the mediastinal mass with the part of the lower lobe of left lung and diaphragm not necessitating a patch repair was performed. The pathological findings were compatible with a diagnosis of a mediastinal hemangioma. Only fibrous adhesions were observed between the tumor and resected lung and diaphragm without any histological invasion. Clinical discussion: While imaging examinations play a key role in determining a preoperative diagnosis, mediastinal hemangiomas may pose a diagnostic challenge mainly due to its rarity. With a clinical suspicion of a hemangioma during the diagnostic work up, a dynamic CT might be helpful. Conclusions: In mediastinal hemangiomas, a preoperative diagnosis is essential in order to avoid extensive surgery. A hemangioma should be raised as a differential diagnosis for anterior mediastinal tumors, especially in cases with an infiltrative appearance that suggests the necessity for a combined resection of the surrounding organs.